Smoldering Combustion - Rein,G (Springer, 2016)
Smoldering combustion is the slow, low temperature, flameless burning of porous fuels and is the most persistent type of combustion phenomena. It is especially common in porous fuels which form a char on heating, like cellulosic insulation, polyurethane foam or peat. Smoldering combustion is among the leading causes of residential fires, and it is a source of safety concerns in industrial premises as well as in commercial and space flights. Smoldering is also the dominant combustion phenomena in megafires in natural deposits of peat and coal which are the largest and longest burning fires on Eartht.